THE TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE MINUTES FROM JUNE 25, 1986 MEETING IN WA, DC (Tufts Archival Research Center, 2007)
Confidential; Minutes from June 25, 1986, meeting of Tobacco Industry Labor Management Committee (LMC). Summarizes the passage of the Packwood Tax Bill without any excise taxes. Reports on federal legislation and federal and local regulations to ban smoking in workplaces, and discusses labor involvement. Presents resolutions supporting the Corporation for Enterprise Development, agreeing to conduct ventilation studies as requested by labor, and supporting labor groups in efforts to draw attention to costs of smoking restrictions.